Asymptotic internal model based coordination of a flywheel energy storage matrix system - Cai , He (Frontiers in Energy Research, 2022)
This paper considers a dual objective distributed coordination problem for a flywheel energy storage matrix system. On one hand, the power output of the entire flywheel energy storage matrix system should track its reference command, which is generated by a linear command generator. On the other hand, the state-of-energy of all the flywheels should be balanced. In contrast to the existing result which employed a common state-of-energy generator as the external model by making use of global system information. By taking advantage of average consensus algorithms, a novel asymptotic internal model based control method is proposed in this paper which eliminates the need of the external model. It is proven that the steady-stateof the asymptotic internal model turns out to be a common state-of-energy generator for all the flywheels under the composite average consensus algorithms, which lends itself to the solution to the dual objective distributed coordination problem. Comprehensive case studies in different scenarios are conducted to examine the performance of the proposed control method.